Design of Parabolic Motion Simulation Using R for Physics Learning - Lisnawati, Lisnawati; Nurhayati, Nurhayati (Universitas Islam Negeri Ar-Raniry, 2026)
Students’ understanding of parabolic motion remains low due to the abstract nature of the concept and the limited use of effective visualization media in learning. This study aims to develop an interactive learning medium in the form of a parabolic motion simulation using the R programming language with the R-Shiny framework, as well as to evaluate its feasibility through expert validation. This research adopts the Research and Development (R&D) method with the Alessi and Trollip model, which includes planning, design, and development stages. The novelty of this study lies in the integration of the R-Shiny framework into physics learning, which is still rarely utilized, particularly for developing interactive simulations at the higher education level. The developed simulation enables dynamic visualization of projectile motion and facilitates exploration of relationships between key variables. The validation results show an Aiken’s V value of 0.99 from media experts and 0.94 from subject matter experts, both categorized as highly valid. These findings indicate that the developed simulation is feasible and effective as an interactive learning medium. It contributes to physics education by enhancing conceptual understanding, promoting active learning, and providing an accessible platform for visualizing two-dimensional kinematics.